2020
DOI: 10.1177/0021998319874502
|View full text |Cite
|
Sign up to set email alerts
|

Improving four-point bending performance of marine composite sandwich beams by core modification

Abstract: The aim of this study was to improve four-point bending performance of foam core sandwich composite beams by applying various core machining configurations. Sandwich composites have been manufactured using perforated and grooved foam cores by vacuum-assisted resin transfer moulding method with vinyl-ester resin system. The influence of grooves and perforations on the mechanical performance of marine sandwich composite beams was investigated under four-point bending test considering the weight gain. Bending str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Load versus crosshead displacement curves of the sandwich specimens with different support spans tested under 3PB and 4PB tests are shown in Figure 2, Figure 3, Figure 4, Figure 5 and Figure 6. All results are also summarised in Table 4, including the initial bending stiffness (K i ), ultimate bending strength (P u ), ultimate bending strength to weight ratio (P u /W), analytical to experimental ultimate bending load ratio (P a /P u ), equivalent bending to effective bending ratio (E eq./ E eff ) and failure modes (related analytical formulations were presented in detail in a previous study 48 ). The analytical loads (P a ) for the sandwich beams were determined using simple beam theory using the mechanical properties of the E-glass/vinyl ester face sheet and PVC foam materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Load versus crosshead displacement curves of the sandwich specimens with different support spans tested under 3PB and 4PB tests are shown in Figure 2, Figure 3, Figure 4, Figure 5 and Figure 6. All results are also summarised in Table 4, including the initial bending stiffness (K i ), ultimate bending strength (P u ), ultimate bending strength to weight ratio (P u /W), analytical to experimental ultimate bending load ratio (P a /P u ), equivalent bending to effective bending ratio (E eq./ E eff ) and failure modes (related analytical formulations were presented in detail in a previous study 48 ). The analytical loads (P a ) for the sandwich beams were determined using simple beam theory using the mechanical properties of the E-glass/vinyl ester face sheet and PVC foam materials.…”
Section: Resultsmentioning
confidence: 99%
“…was determined using the deflection formula obtained from the experimental results for sandwich beams. 9,15,21,48
Figure 2.Load-crosshead displacement curves of SB1 specimen, (a) L: 120 mm, 3PB, (b) L: 180 mm, 3PB, (c) L: 300 mm, 3 point, (d) L: 450 mm, 3PB, (e) L: 450 mm, 4PB, (f) Failure mode at 4PB test.
Figure 3.Load-crosshead displacement curves of SB2 and SB4 specimens, (a) L: 120 mm, 3PB, (b) L: 180 mm, 3PB, (c) L: 300 mm, 3PB, (d) L: 450 mm, 3PB, (e) L: 450 mm, 4PB, (f) Failure modes of SB2 and SB4 specimens at 4PB test.
Figure 4.Load-crosshead displacement curves of SB3 specimen, (a) L: 120 mm, 3PB, (b) L: 180 mm, 3PB, (c) L: 300 mm, 3PB, (d) L: 450 mm, 3PB, (e) L: 450 mm, 4PB, (f) Failure modes of SB3 specimens tested at 3PB and 4PB flexural up and down tests.
Figure 5.Load-crosshead displacement curves of AB1 specimen, (a) L: 120 mm, 3PB, (b) L: 180 mm, 3PB, (c) L: 300 mm, 3PB, (d) L: 450 mm, 3PB, (e) L: 450 mm, 4PB, (f) Failure modes of AB1 specimens tested at 4PB flexural up and down tests.
Figure 6.Load-crosshead displacement curves of AB2 specimen, (a) L: 120 mm, 3PB, (b) L: 180 mm, 3PB, (c) L: 300 mm, 3PB, (d) L: 450 mm, 3PB, (e) L: 450 mm, 4PB, (f) Failure modes of AB2 specimens tested at 4PB flexural up and down tests.
…”
Section: Resultsmentioning
confidence: 99%
“…The price of the foam and epoxy resin are 852.00 $/m 3 and 4662.71 $/m 3 , respectively. A typical thickness of 25 mm, which was commonly adopted in [15,19,22,23,26], was decided as the target thickness of the foam for evaluating the cost of infused cores. The fractions of infused resin were 0.00%, 1.08%, and 6.20% in volume for the plain, GP, and GPC cores, respectively.…”
Section: Cost Evaluationmentioning
confidence: 99%
“…Balıko glu et al [26] investigated the effect of perforated and grooved foam core modification on the bending performance of composite sandwich beams made of E-glass fibre/vinylester resin composite face sheets and closed cell PVC foam. The experimental results showed that the bending strength and effective stiffness of sandwich beam increased by 34% and 61%, respectively, compared with that without core modification.…”
Section: Introductionmentioning
confidence: 99%
“…The final composition of a sandwich structure depends on the target application. For example, polymer foam cores are generally used in car flooring, boat parts, as well as turbine blades, as they have good rigidity, high strength, and resistance to fatigue and temperature [ 12 , 13 , 14 , 15 ]. Feng and Aymerich [ 13 ] studied the effect of the density of a polyvinyl chloride (PVC) foam core on sandwich panels with carbon/epoxy-laminated facings, resulting in a composite structure with excellent stiffness.…”
Section: Introductionmentioning
confidence: 99%